THE LONG‐TERM EFFICACY OF ACUTE‐PHASE PSYCHOTHERAPY FOR DEPRESSION: A META‐ANALYSIS OF RANDOMIZED TRIALS. Issue 5 (21st March 2016) - Karyotaki, Eirini; Smit, Yolba; de Beurs, Derek P.; Henningsen, Kirsten Holdt; Robays, Jo; Huibers, Marcus J. H.; Weitz, Erica; Cuijpers, Pim
Abstract : Background: Understanding the effectiveness of treatment for depression in both the short term and long term is essential for clinical decision making. The present meta‐analysis examined treatment effects on depression and quality of life in acute‐phase psychotherapeutic interventions compared to no treatment control groups for adult depression at 6 months or longer postrandomization. Methods: A systematic literature search resulted in 44 randomized controlled trials with 6, 096 participants. Acute‐phase psychotherapy was compared to control groups at 6‐month or longer postrandomization. Odds ratios of a positive outcome were calculated. Results: Psychotherapy outperformed control groups at 6 months or longer postrandomization (OR = 1.92, 95% CI: 1.60–2.31, P < .001). Heterogeneity was moderate ( I ²: 65, 95% CI: 53–74, P < .001). However, effects significantly decreased with longer follow‐up periods. Additionally, a small positive effect of psychotherapy was observed for quality of life, while similar effects were obtained in separate analyses of each type of psychotherapy, with the exception of nondirective supportive therapy. Studies that provided booster sessions had better treatment results compared with studies that did not provide any further sessions. Finally, we found that trials on psychotherapy aimed at major depressive disorder (MDD) had better outcomes than those that were aimed at elevated depressive symptoms. Conclusions: There is substantial evidence that acute‐phase psychotherapy results in a better treatment effects on depression and quality of life in the long term for adult patients with depression.